A complementary metal oxide semiconductor low noise amplifier using integrated active inductor - Khamis @ Roslee, Rafiq Sharman (2007)
Low Noise Amplifier (LNA) is a very important component in a receiver system. It provides the smallest noise and high gain to decrease the noise of the subsequent stages and the whole system. As System On Chip (SOC) is very important nowadays, active inductor is an alternative to the designer to have an integrated design. Furthermore, active inductor can be tuned to obtain the required inductance and Q-factor values. Instead of using passive inductor such as spiral and bonding wire which need bigger die area, active inductor can be employed to save die area but this comes at the cost of higher current consumption and noise. This thesis presents the study of active inductor architecture, how active inductor can combine with LNA and evaluation on LNA performance when active inductor is added. This will help designers to have better understanding on how to use active inductor in their design. This research proposes the Commmon Gate LNA architecture and is designed with 1.2 um CMOS process, operating at 850 MHz. The voltage gain and noise factor obtained are 24.7 dB and 8.26 dB respectively. Two active inductors are used as gain control, input and output matching of LNA. However, the LNA consumes 163.8 mW where 75% percent of power consumption is contributed by active inductor.